Bloom or bust: synchrony in jellyfish abundance, fish consumption, benthic scavenger abundance, and environmental drivers across a continental shelf. (11th July 2016) - Smith, Brian E.; Ford, Michael D.; Link, Jason S.
Abstract: Increases in gelatinous zooplankton (GZ) populations, their dominance of some ecosystems, their impacts to other taxa, and their questionable trophic value remain global concerns, but they are difficult to quantify. We compared trends in GZ abundance from direct sampling for the northeast U.S. continental shelf and tested their association with GZ consumption by spiny dogfish ( Squalus acanthias ); the abundance of two benthic scavengers: Atlantic hagfish ( Myxine glutinosa ) and grenadiers (Family: Macrouridae); and four environmental indices: Atlantic Multidecadal Oscillation, North Atlantic Oscillation, and sea surface and bottom temperatures. Defined as scyphozoans, siphonophores, ctenophores, and salps, the abundance of GZ on the shelf has oscillated with blooms approximately every 10–15 yr. Conservative estimates of annual removal of GZ by spiny dogfish ranged from approximately 0.3–298 g individual −1 with spiny dogfish being the primary GZ feeder sampled on the shelf. The examination of three abundance series for GZ identified one shelf‐wide trend and strong relationships with 2‐yr lagged consumption and scavenger abundance (namely hagfish), and sea surface temperature. With multimodel inference, these covariates led to an optimal model of GZ abundance. Blooms of GZ abundance on this shelf were influenced by environmental change, provide surges of food for spiny dogfish, and may offer 'food falls' for scavenging fishes. The bioenergetic tradeoffs of consuming greater amounts of GZ compared to other major prey (e.g., fishes) remain unknown; however, these surges of food in the northwest Atlantic appear to be important for fishes, including support for benthic scavenger productivity.